Student Perception of Interest in Learning and its Impact on Online Learning of Public Health Study Program, University of Muhammadiyah Jakarta - Indah Nofita; Karimah Azzahra; Lentera Mahameru Kaffah; Nabilah Nur Haenisa; Munaya Fauziah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
In Indonesia, a large-scale social restriction policy or commonly known as PSBB has been implemented to further suppress the spread of this virus in Indonesia. The education sector is changing due to the Covid-19 pandemic. The government through the Letter of the Minister of Education and Culture Number 36962 / MPK.A / HK / 2020 concerning Online Learning and Working from Home to Prevent the Spread of Covid-19 as an effort to prevent the spread of Covid-19. The Learning System has changed from face-to-face to online where this research was conducted at the Faculty of Public Health, the University of Muhammadiyah Jakarta in 2021. The objective of this study was to determine student perceptions regarding online learning during the Covid-19 period. Descriptive research method design with a qualitative approach with phenomenological methods. The sample in this study was four (4) students consisting of one second semester, one fourth semester, and two sixth semesters. This study wants to explore the phenomena experienced by students in online learning during the COVID-19 pandemic. The variables studied include behavior, perception, motivation, action and some of them are grouped into learning impacts, physical linkages, infrastructure, and holistic Islamic practices experienced by students in online learning. The result from The impact of learning is that students feel less interested in learning, less effective, and less understanding. From a physical point of view, eye fatigue is felt, from facilities and infrastructure students feel signal barriers when doing online learning from parental support to support online learning and from Islamic practice in the learning process carried out by several lecturers, in terms of decreased motivation to learn students experience decreased motivation to learn, in terms of student satisfaction, they are not satisfied and want offline learning.